Wave exciting forces of a free floating semi submersible in regular waves - Abyn, Hassan (Penerbit UTM Press, 2015)
Drilling and production of oil by semi submersible take place in many locations throughout the world. Generally, floating structures play an important role in exploring the oil and gas from the sea. The force and motion prediction of offshore structures may be carried out using time domain or frequency domain models or model tests. In this paper the frequency domain analysis used because it is the simplified and linearized form of the equations of motion. The time domain analysis, unlike frequency domain models, is adequate to deal with non-linearities such as viscous damping and mooring forces, but it requires sophisticated solution techniques and it is expensive to employ. In this paper, the wave exciting forces of a free floating semi-submersible were carried out using 3D source distribution method within the scope of the linear wave theory. The results obtained from computations were also compared with the results obtained using commercial software MOSES and WAMIT.